MODEL DUKUNGAN INSTITUSIONAL DALAM DINAMIKA MOTIVASI INTRINSIK, BIMBINGAN DOSEN, DAN KUALITAS PUBLIKASI PENELITIAN - Andriani, Idaya; Gafar Alamsyah; Eka Apriani; Jumira Warlizasusi; Asri Karolina (STAI Ma'had Aly Al-Hikam Malang, 2024)
Research publications are an important aspect of a student's academic journey. Publications can broaden knowledge horizons, share research findings, and strengthen academic reputation. The aim of this research is to build a conceptual model of institutional support for students research publications by examining the influential interactions between the variables of institutional support, students' intrinsic motivation, lecturer guidance, and the quality of research publications. Based on these four variables, six hypotheses were formulated. This quantitative research method uses the Partial Least Squares Structural Equation Model (PLS-SEM) to evaluate the hypothesis model. A total of 124 postgraduate students from IAIN Curup were involved as participants to fill out questionnaires which have been proven to be valid and reliable. Data were analyzed using the SmartPLS application to evaluate measurement models and structural models. The research results show that institutional support and lecturer guidance significantly increase the intrinsic motivation and quality of student research and publications. Support from educational institutions significantly increases students' intrinsic motivation, which in turn improves the quality of research and publications. Institutional support also directly improves the quality of research. High-quality faculty-student relationships significantly increase intrinsic motivation and academic quality. In addition, institutional support for lecturers increases the effectiveness of teaching and guidance. These findings confirm the conceptual model of institutional support that has been developed and tested in increasing intrinsic motivation, lecturer guidance, and the quality of student publications. Keywords: Lecturer Guidance; Institutional Support; Publication Quality; Intrinsic Motivation. ABSTRAK Publikasi penelitian merupakan aspek penting dari perjalanan akademik mahasiswa. Publikasi dapat memperluas cakrawala pengetahuan, berbagi temuan penelitian, dan memperkuat reputasi akademik. Tujuan Penelitian ini adalah untuk membangun model konseptual dukungan institusi terhadap publikasi penelitian mahasiswa dengan memeriksa interaksi yang berpengaruh di antara variabel dukungan institusi, motivasi intrinsik mahasiswa, bimbingan dosen, dan kualitas publikasi penelitian. Berdasarkan keempat variabel tersebut, enam hipotesis dirumuskan. Metode penelitian dengan kuantitatif ini menggunakan Model Persamaan Struktural Partial Least Squares (PLS-SEM) untuk mengevaluasi model hipotesis. Sebanyak 124 mahasiswa pascasarjana dari IAIN Curup terlibat sebagai peserta untuk mengisi kuesioner yang telah terbukti valid dan reliabel. Data dianalisis menggunakan aplikasi SmartPLS untuk mengevaluasi model pengukuran dan model struktural. Hasil penelitian menunjukkan bahwa dukungan institusi dan bimbingan dosen secara signifikan meningkatkan motivasi intrinsik dan kualitas penelitian serta publikasi mahasiswa. Dukungan dari institusi pendidikan secara signifikan meningkatkan motivasi intrinsik mahasiswa, yang pada gilirannya meningkatkan kualitas penelitian dan publikasi. Dukungan institusi juga secara langsung meningkatkan kualitas penelitian. Hubungan dosen-mahasiswa yang berkualitas tinggi secara signifikan meningkatkan motivasi intrinsik dan kualitas akademik. Selain itu, dukungan institusi untuk dosen meningkatkan efektivitas pengajaran dan bimbingan. Temuan-temuan ini mengkonfirmasi model konseptual dukungan institusi yang telah dikembangkan dan diuji dalam meningkatkan motivasi intrinsik, bimbingan dosen, dan kualitas publikasi mahasiswa. Kata kunci: Bimbingan Dosen; Dukungan Institusi; Kualitas Publikasi; Motivasi Intrinsik.